1998
DOI: 10.1111/j.1600-0722.1998.tb02202.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical detection of apoptosis in human odontoblasts

Abstract: Eur J Oral Sci /998. 106 (supp/1 ). 384 387 P,.inted in UK. All rights resen ed Immunocytochemical detection of apoptosis in human odontoblasts Franquin J-C. Remusal M, Abou Hashieh I, Dejou J: lmmunocylochemical detection of apoptosis in human odontoblasts. Eur J Oral Sci 1998: 106 (suppl 1): 384 387. Eur J Oral Sci , 1998Pulpal chamber ize decrea es on ageing due to primary and secondary dentin deposition . This work was designed to find out the con equences of thi pulp chamber reduction on odontobla t numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 8 publications
2
36
0
Order By: Relevance
“…Continuous dentin deposition progressively decreases both the volume occupied by the pulp fibroblasts and the dentin/odontoblast interface. The only study dealing with this physiological event has shown that massive odontoblast apoptosis occurs during a 4-year period [15]. To confirm these previous studies we have measured the number of odontoblasts in a given surface of 10, 11, 12.5 and 14 year-old premolars.…”
Section: Organization Of Odontoblasts Within the Pulp Chamber In Intamentioning
confidence: 84%
See 4 more Smart Citations
“…Continuous dentin deposition progressively decreases both the volume occupied by the pulp fibroblasts and the dentin/odontoblast interface. The only study dealing with this physiological event has shown that massive odontoblast apoptosis occurs during a 4-year period [15]. To confirm these previous studies we have measured the number of odontoblasts in a given surface of 10, 11, 12.5 and 14 year-old premolars.…”
Section: Organization Of Odontoblasts Within the Pulp Chamber In Intamentioning
confidence: 84%
“…In another experimental set, cavity preparations were performed as previously described in 17 premolars of 11 to 12 year-old patients [15], while 4 intact premolars were used as a control. A dental product (IRM) was used to restore the cavities, in conjunction with a calcium hydroxide lining material (Dycal, Dentsply, Milford, DE, USA).…”
Section: Preparation Of Teethmentioning
confidence: 99%
See 3 more Smart Citations